English Language - Laksono, Shafa Monica; Rukmi, Wara Indira; Parlindungan, Johannes (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Urban public space, including village public spaces, is formed by social construction in its environment. This sociability of community has its own social value. In the urban kampung, the local community and the children took a deal to adapt to the environment. Therefore, the children create their own play spaces. Kampung Warna-Warni has unique characteristics such as being located in a steep topography around the Brantas River basin, as a thematic tourism village, and as a community housing with hight density levels of the building. The focus of the research is developing the realization of a child-friendly space by taking into account the needs of other public space users. This research used a qualitative method by descriptive approach. This reports the findings of children's play patterns in Kampung Warna-Warni, patterns of public space utilization, and evaluation based on child-friendly space parameters. We examined this study by using descriptive analysis including observing children's playing patterns through behavior maps and evaluating the parameters of child-friendly space. Our findings in this study reveal that Kampung Warna-Warni is a child-friendly play space because children have the freedom to play in terms of accessibility, comfort, safety, and availability of facilities. However, according to the parents of the children, there are concerns about the safety aspect when children play around the river. Nevertheless, the freedom to play for children is the main thing in establishing child-friendly play spaces.